PENGENDALIAN PERLADANGAN BERPINDAH DENGAN AGROFORESTRI BERBASIS TANAMAN DAMAR DI DESA IMABATAI KECAMATAN INAMOSOL KABUPATEN SERAM BAGIAN BARAT - Matinahoru, Johan Markus (MAANU: Jurnal Pengabdian Kepada Masyarakat, 2024)
Shifting cultivation is an agricultural system that is widely practiced by farmers because it does not require much capital for its activities. However, the impact of shifting cultivation activities is quite large, especially on forest destruction. To control the impact of shifting cultivation practices is to introduce the agroforestry model to farmers. Agroforestry is a farming model that combines agricultural crops and forestry crops. The aim of the activity is to provide insight and understanding to farmers/cultivators who practice shifting cultivation so that they can reduce shifting cultivation activities. A total of 20 representatives from 20 families or 25% of the total number of families in Imabatai village were involved in intensive activities. This activity also involved female representatives, namely 10 people representing 10 families, while 10 men were involved representing 10 families. Participants really responded to this training, because it was something new for farmers. So far, participants have focused more on agricultural systems that rely more on business patterns that only focus on agricultural crops. Apart from that, the aspect of understanding the training material was very good, because 85% of participants were able to answer the evaluation questions well. The future hope is that participants can immediately try to practice agroforestry or dusung because it is very promising to increase farmers' income in the future when harvest time comes. Apart from that, agroforestry practices can reduce the impact of shifting cultivation which leads to the formation of critical land.